The Tourism School Students’ Learning Engagement during COVID-19 Pandemic - Sutanto Leo (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2023)
This study aims to investigate students’ learning engagement during the pandemic. A mixed method design was used by combining a questionnaire and in-depth interviews. The quantitative data analysis used descriptive statistics and the Likert scale. The qualitative data analysis used thematic analysis technique. The findings indicate that most aspects of learning engagement are reasonably feasible, but there is a need to reduce the learning workload. The in-depth interviews of the online technology utility are effective to some degree. Internet network should be improved, the workload and the duration on the phone screens should be reduced to make students less exhausted.